Nonunique Fixed Point Results via Kannan F-Contraction on Quasi-Partial b-Metric Space. (2nd November 2021) - Gautam, Pragati; Kumar, Santosh; Verma, Swapnil; Gupta, Gauri
Abstract : This paper is aimed at acquainting with a new Kannan F -expanding type mapping by the approach of Wardowski in the complete metric space. We establish some fixed point results for Kannan F -expanding type mapping and F -contractive type mappings which satisfy F -contraction conditions. Additionally, some new results are given which generalize several results present in the literature. Moreover, some applications and examples are provided to show the practicality of our results.